Gas detection with the influence of a coal layer using a variational mode decomposition–Based highlight volumes extraction method in a tight sandstone reservoir - Wang, Xing-Jian; Xue, Ya-Juan (Frontiers in Earth Science, 2022)
The low-frequency strong reflection of coal seams always makes the gas detection of the adjacent gas reservoir difficult in a tight sandstone reservoir. An adaptive decomposition processing approach is introduced in this study to inspect the ability to target the weak seismic response of the gas reservoirs interfered by the adjacent coal seams. The variational mode decomposition (VMD)-based highlight volumes extraction approach is used to better detect the weak seismic response of the gas reservoirs concealed by the adjacent strong reflection of coal seams in a tight sandstone reservoir. The amplitudes above the average and peak frequency volumes are extracted from each intrinsic mode functions after VMD for gas detection. Field data examples show that the VMD highlights the weak seismic responses of the geological and stratigraphic information and hydrocarbon-related contents. The results obtained from the VMD-based highlight volumes extraction approach are in close agreement with previous logging interpretations and the drilling information of wells, and the lateral extent of hydrate-bearing strata is estimated with increased accuracy. When the influence of the strong reflection amplitudes caused by the coal seams is not suppressed, the characterization of the weak seismic responses in the reservoirs would prevent the detection of gas or overestimate the lateral distribution of the gas strata. The adaptive decomposition processing methodology has the ability to detect the weak seismic responses in reservoirs interfered or concealed by adjacent coal seams and yields a better hydrocarbon-related interpretation.